The Effect Of Mitragynine On Cyclic Amp Formation And Mrna Expression Of Mu-Opioid Receptors Mediated By Chronic Morphine Treatment In Sk-N-Sh Neuroblastoma Cell - Jamil, Mohd Fadzly Amar (2013)
Mitragynine is an indole alkaloid compound of Mitragyna speciosa (M.speciosa) Korth. (Rubiaceae). In Thailand, this plant is known as “Kratom” and in Malaysia it is known as “Biak-biak” or “Ketum”. M. speciosa was used as substitution therapy for chronic opioid treatment to manage the withdrawal symptoms in Malaysia and Thailand. To date over 40 compounds have been isolated from the leaves of this plant. Mitragynine is the most abundant of the more than 25 alkaloids of Kratom (66% of the crude base) and is responsible for the substance’s opioid effects. The bioactive compound mitragynine from M.speciosa was isolated using acid-base extraction followed by a column chromatography method. In this study, we had investigated the cellular mechanism of chronic morphine treatment after co- and pre-treatment with mitragynine in production of forskolin stimulation cyclic adenosine monophosphate (cAMP) and expression of mu-opioid receptor (MOR) during the differentiation of SK-N-SH human neuroblastoma cells, the possible mechanisms involved in those changes, and the differential effects of morphine and mitragynine. cAMP is a molecule that is controlled by G protein-coupled receptor activation and other cellular processes. Measurement of cAMP levels in cell is widely used as an indicator of receptors function in drug discovery application.